Dental health education for elementary school students with promotive and preventive methods in Padang City - Laelia Dwi Anggraini; Leny Sang Surya; Muhammad Bakhrul Lutfianto; Atiek Driana Rahmawati; M Fadli (Universitas Muhammadiyah Magelang, 2023)
As many as 54% of children aged 5-9 years have cavities, damaged or diseased teeth. But only 14.6% of these children received treatment from dental medical personnel. This shows that public awareness of dental and oral health is low. The purpose of this community service is to increase dental and oral health knowledge to prevent an increase in the number of dental and oral problems in SD Negeri 44 Sungai Lareh, Koto Tangah, Padang City. The method used in this community service is counseling and tooth brushing which attended by 147 elementary school children. The results of the program showed an increase in awareness regarding general health knowledge, dental and oral health after counseling by 21%.